Analisis Implementasi Good Corporate Governance dan Etika Bisnis dalam Meningkatkan Kinerja Keuangan di PT Bank Mandiri (Persero) Tbk - Muhammad Whindo Langgeng Rachmadiar; Mohamad Afrizal Miradji; Muhammad Arya Arditya Rangga; Mohammad Ilham Ardiansyah; Jovian Argitama (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of implementing Good Corporate Governance (GCG) and business ethics on the financial performance of PT Bank Mandiri (Persero) Tbk. The study employs a quantitative method with a descriptive-verificative approach, using secondary data from the financial and governance reports of Bank Mandiri for the 2021–2023 period. Data were analyzed using multiple linear regression supported by classical assumption tests, the t-test, F-test, and coefficient of determination (R²).The findings reveal that both GCG and business ethics positively and significantly influence financial performance, either partially or simultaneously. An increase in GCG and business ethics scores contributes to improvements in Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM).